Effects of Covid-19 Among School Adolescents in Kween District - Oonyu, Isaac Job; Sam, Cherop; Ajilong, Joyce; Mugisha, Lillian Kamanzi (Heroes for Gender Transformative Action, 2022)
The ISPHD programme (Heros4GTA) is a joint district-based programme implemented by the consortium of Amref Health Africa in Uganda, Cordaid, MIFUMI, and the International Centre for Research on Women (ICRW) for the period 2020-2024 in the 9 High Burden Districts1 of Uganda with funding from The Embassy of the Kingdom of the Netherlands Kampala. The program participants include young adolescents (age 10-14) and women (age 15-49), hardly introduced to information on SRHR and the need to have gender equality. Key to the intervention is the gender-transformative education (GTE) to enhance access to SRHR/SGBV services and to work with the communities they live in to reject cultures and norms that cause SGBV. It is against this this study was undertaken to find out how Covid-19 and the lockdown has affected young people especially those in school in order to inform relevant interventions, planning and implementation through solicitation of stakeholders at individual, community and service points. The findings from this study will form the basis of setting modalities of strengthening approaches to protect young people particularly girls from the vulnerability registered as a result of Covid-19 and the lockdown. It therefore provide evidence for better decision making and further advocacy.